Flow enhancement in pipeline transportation for heavy crude oil emulsion - Nurul Hafiza, Norden (2014)
Stable concentrated oil in water (01W) emulsions was prepared and their application for heavy oil pipeline transportation was investigated using very viscous Malaysian heavy crude oil. Malaysian heavy crude oil samples namely Miri were used to produce heavy crude oil- in-water emulsions. Historically, demand for heavy and additional-heavy oil has been marginal because of their high viscosity and composition complexity that make them hard and expensive to produce, transport and refine. Presently, there are three general approaches for transportation of heavy and extra heavy oil which are viscosity reduction, drag minimization and in-situ oil enhancement This 3 conventional method required high cost. Hence, our scope of study approached is to convert the 95% of w/o in pipeline to o/w technique by using the advantage of water to carry the oil This method is a promising cost effective and shorten the time of the transportation The expected result based on the reference was revealed that the stability of the oil-in-water emulsion stabilized by Triton X-100 increased as the surfactant concentration increases, with a consecutive decrease in the crude oil—water interfacial tension (IFT). Larger the oil content, the speed and duration of mixing, while increases in the temperature of the homogenization process substantially reduced the viscosity of the prepared emulsions.